Curriculum Implementation in Elementary School Learning: Challenges, Strategies, and Its Implications for Educational Qualit - Romi Laspita; Maliny Putri; Sintia Aprilia; Herlina Safitri; Miftahul Jannah; Suci Rahmadani; Nur Annisa; Novi Adelia; Raty Fitriani; Amelia Febriani; Dinia Ahira Fitrah (The Future of Education Journal, 2026)
Curriculum implementation is an important component in achieving educational goals and improving learning quality in elementary schools. Effective curriculum implementation enables teachers to organize learning activities systematically while facilitating students in developing knowledge, skills, and character. This study aims to analyze the challenges, strategies, and implications of curriculum implementation in elementary school learning. The method used in this study is a literature review by examining various scientific articles, books, and relevant research reports. The findings indicate that curriculum implementation in elementary schools faces several challenges, including limited teacher competence, inadequate educational facilities, differences in student characteristics, and changes in educational policies. To address these challenges, various strategies can be implemented, such as improving teacher professionalism through training programs, developing innovative learning models, utilizing educational technology, and strengthening collaboration among schools, parents, and communities. Effective curriculum implementation contributes positively to educational quality by improving learning outcomes, fostering critical thinking skills, enhancing student engagement, and supporting character development.